Lipid-lowering properties of protein-rich mucuna product. Issue 1 (December 2016) - Ngatchic, Josiane; Njintang, NicolasYanou; Bernard, Clemence; Oben, Julius; Mbofung, Carl
Abstract Background The objective of this study is to evaluate the effect of protein-rich mucuna product (PRMP) on lipid parameters of hyperlipidemic rats. Methods Hyperlipidemia was induced in male rats for 3 weeks through high-fat diet. After induction, 30 hyperlipidemic rats were divided into five groups of six rats: control group (CG) received casein and four groups received PRMP as protein source at different proportions: 8.2, 16.4, 24.6, and 32.8 % corresponding, respectively, to 25, 50, 75, and 100 % substitution of casein in the diet for 3 weeks. Lipid and oxidative stress parameters of rats were assessed. Results There were no significant differences in food intake and body weight loss among the experimental groups. The concentrations of the serum low-density lipoprotein cholesterol, total cholesterol, and triglycerides were lower in groups fed on PRMP 50, 75, and 100 % than in the CG group (p  < 0.05). Histological analysis of the liver revealed that animals fed on PRMP diets presented a lower level of steatosis than the CG group. The most significant reduction of lipid parameters was obtained when PRMP was used as unique source of protein (PRMP 100 %). PRMP also influenced oxidative stress parameters as evidenced by a decrease in malondialdehyde and an increase in catalase and superoxide dismutase. Conclusions These findings demonstrated that PRMP exerts hypolipidemic effect; it has a metabolic effect on endogenous cholesterol metabolism and a protector effect on the development of hepatic steatosis. Our results also suggest that PRMP could manage metabolic diseases associated with oxidative stress.